APPROACHES FOR SUSTAINABLE CAMPUS PARKING MANAGEMENT AT THE YTU CENTRAL CAMPUS AREA - Yardim, Mustafa Sinan (YILDIZ TECHNICAL UNIV, 2015)
An important way to sustainable solutions for parking problems at existing university campus areas lies beneath the correct analysis of user behaviors and campus forms. This approach has been the experienced at the Yildiz Technical University (YTU) campuses. A questionnaire has been prepared and performed to several groups for determining user behaviors and parking problems at the campuses. In this study, different years the results of YTU Campuses Parking Problems Questionnaire's data, obtained specifically from YTU Central Campus has summarized. Depending on site data and information from the results of the questionnaire which made in 2009 a parking plan had been developed in the year 2010 and gradually implemented. The effects of this implementation had been observed by the repeated questionnaires in the years 2011 and 2012. In this article, also, obtained experiences during this process and some recommendations are given.
Keywords: University campus; YTU; sustainability; campus parking; parking management; Engineering